A review on mushroom-derived bioactive peptides: Preparation and biological activities. (August 2020) - Zhou, Juanjuan; Chen, Mengfei; Wu, Shujian; Liao, Xiyu; Wang, Juan; Wu, Qingping; Zhuang, Mingzhu; Ding, Yu
Graphical abstract: Highlights: Mushrooms are promising sources of bioactive peptides. Endogenous peptides have been proposed as the main active form. Mushroom-derived ACE inhibitory peptides have been intensively investigated. Mushroom-derived antioxidant peptides are actively studied but lack of identification. Abstract: Mushroom bioactive peptides (MBAPs) refer to bioactive peptides extracted directly or indirectly from mushrooms or their mycelia. Owing to the presence of a large quantity of high-quality proteins, many mushrooms are promising sources of bioactive peptides. The beneficial effects, including antihypertensive, antioxidant, and antimicrobial activities, of MBAPs are being increasingly recognized with regards to health promotion and disease prevention. However, this field is relatively undeveloped and relevant reviews are scarce. Hence, the aim of this review was to present the current research status of MBAPs, focusing on their preparation and biological functions. An insight regarding the direction of future research has been also discussed.